Household-Level Environmental Exposure in Rural Arctic Alaska: An Integrated Assessment of Water, Soil, and Indoor Air - Valentin Romanovski; Somayeh Asadi; Parham Azimi; Zahra Keshavarz; Cody McIntyre; Donovan Johnson; Joseph G. Allen (Environmental Research, 2026)

Effects of residential ventilation and filtration interventions on adult asthma outcomes - Insung Kang; Anna McCreery; Parham Azimi; Mingyu Wang; Amanda Gramigna; Griselda Baca; Timothy Crowder; Rachel Scheu; Anne Evens; Brent Stephens (Building and Environment, 2025)

Air quality and health benefits of achieving carbon-neutrality in building sector over Beijing, China - Mengya Wang; Yingying Liu; Sumei Li; Parham Azimi; Sha Chen; Steve Hung Lam Yim (Journal of Environmental Management, 2024)

Exposure assessment of metal(loids) in indoor air and biomonitoring in six urban residential areas in Iran - Zahra Soleimani; Parham Azimi; Rosa Haghshenas; Yosef Farzi; Ali Taherkhani; Kazem Naddafi; Masud Yunesian; Maryam Naserinjad; Amir Hossein Behnoush; Marzeih Parizad; Maryam Keyvani; Amirali Hajebi; et al. (Science of The Total Environment, 2024)

Correction to: Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)
The article Microbial Exchange via Fomites and Implications for Human Health, written by Brent Stephens, Parham Azimi, Megan S. Thoemmes, Mohammad Heidarinejad, Joseph G. Allen, and Jack A. Gilbert, was originally published electronically on the publisher’s internet portal

Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)

Predicting Concentrations of Ultrafine Particles and Volatile Organic Compounds Resulting from Desktop 3D Printer Operation and the Impact of Potential Control Strategies - Parham Azimi; Torkan Fazli; Brent Stephens (Journal of Industrial Ecology, 2017)
Summary Recent studies have shown that potentially hazardous volatile organic compounds (VOCs) and ultrafine particles (UFPs) are emitted from many desktop three‐dimensional printer and filament combinations. We use recently published measurements of UFP and speciated VOC emission rates from a number of desktop 3D printers and filaments to predict the magnitudes of human exposures to airborne pollutants that would be expected in multiple locations within a typical small office environment. We also model the impacts of several control strategies for reducing occupational exposures. Results demonstrate that UFP and VOC concentrations within close or moderate proximity (i.e., within 3 and 3 to 18 meters, respectively) to some desktop 3D printer and filament combinations with the highest emissions can exceed recommended exposure levels (RELs) for some VOCs and typical indoor concentrations for both UFPs and VOCs. Concentrations of caprolactam within close proximity to a printer using some nylon‐based filaments are predicted to exceed both acute and chronic RELs set by the California Office of Environmental Health Hazard Assessment. UFP concentrations are predicted to reach as high as 80,000 particles per cubic centimeter in close proximity to the highest emitting printer and filament combinations. The printer and filament combinations with the lowest UFP and VOC emission rates are not expected to yield concentrations at levels of concern. The most effective control strategies for reducing both UFP and VOC concentrations included installing a high‐flow spot ventilation system and operating the printer in a sealed enclosure with high‐efficiency gas and particle filtration.